Analysis of Chemical Compounds of Agarwood Oil based on Headspace-Solid Phase Microextraction combined with Gas Chromatography Mass-Spectrometry - Nurlaila, Ismail; Mohd Hezri, Fazalul Rahiman; Mod Nasir, Taib; Nor Azah, Mohd Ali; Mailina, Jamil; Saiful Nizam, Tajuddin (2013)
The quality of the agarwood oils plays an important role as it reflects the price of the oil in the market. High quality agarwood oil is traded extensively. In order to obtain good quality agarwood oil, temperature condition during the extraction is one of the important parameter instead of type and time of extraction. An analysis of chemical compounds of agarwood oil involves of three different temperature conditions such as 40°C, 60°C and 80°C has been carried out in this study. The analytical work involves HS-SPME combined with GC-MS analysis to extract and identify the chemical compounds composition in agarwood oil. The zscore technique was introduced to identify the significant compounds that contribute to the aroma of agarwood oil. The result shows that five compounds were identified and they were aromadendrane, β-agarofuran, α-agarofuran, 10-epi-□-eudesmol and □-Eudesmol. These compounds were found to have similar pattern of plot but different in chemical composition due to the different chemical properties of the oils.